2011
DOI: 10.1056/nejmoa0912696
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon plus Adefovir versus Either Drug Alone for Hepatitis Delta

Abstract: Treatment with peginterferon alfa-2a for 48 weeks, with or without adefovir, resulted in sustained HDV RNA clearance in about one quarter of patients with HDV infection. (Current Controlled Trials number, ISRCTN83587695.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
410
3
36

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(458 citation statements)
references
References 38 publications
(44 reference statements)
9
410
3
36
Order By: Relevance
“…Treatment with this type of IFN induced rates of sustained virological responses that varied from 17% to 43%4-6 However, these studies also included only a small number of patients and are difficult to compare because of the clinical heterogeneity of the patients; the highest rates of sustained virological response were reported in a series of 14 patients, most of whom did not have cirrhosis (a common complication in patients with HDV). 5 The paper by Wedemeyer and coworkers 7 provides information on what can be achieved with PEG-IFN-2a in patients infected with HBV and HDV. Wedemeyer et al compared the efficacy of PEG-IFN-2a alone versus its combination with adefovir and adefovir monotherapy.…”
mentioning
confidence: 99%
“…Treatment with this type of IFN induced rates of sustained virological responses that varied from 17% to 43%4-6 However, these studies also included only a small number of patients and are difficult to compare because of the clinical heterogeneity of the patients; the highest rates of sustained virological response were reported in a series of 14 patients, most of whom did not have cirrhosis (a common complication in patients with HDV). 5 The paper by Wedemeyer and coworkers 7 provides information on what can be achieved with PEG-IFN-2a in patients infected with HBV and HDV. Wedemeyer et al compared the efficacy of PEG-IFN-2a alone versus its combination with adefovir and adefovir monotherapy.…”
mentioning
confidence: 99%
“…In 2006 three small studies could show effectiveness for this type of treatment [41][42][43] , but nevertheless SVR rates remained low (17% to 43%) overall. In a multicentre randomised landmark trial published in 2011, Wedemeyer et al [44] achieved 28% SVR. These differences in SVR rates compared to prior smaller trials might be due to baseline clinical, demographical and virological characteristics [30] .…”
Section: Treatment Of Delta Hepatitismentioning
confidence: 99%
“…The latter could possibly benefit from a prolonged treatment, because HDV decrease might occur late, even after the end of treatment [44] . Clear predictors of response to IFN have not been identified, but viral load determination at 6 mo of treatment might be helpful [41,43] .…”
Section: Treatment Of Delta Hepatitismentioning
confidence: 99%
“…In addition, clevudine could cause severe myopathy by depletion of mitochondrial DNA as side effect [77]. A multicenter randomized study (HIDIT I) compared the efficacy of peg-IFN alpha-2a plus adefovir versus peg-IFN alpha-2a plus placebo versus adefovir in chronic HDV infection [78]. 72-week results of this study showed that peg-IFN alpha-2a had a significant antiviral effect for HDV in more than 40% of patients, HDV-RNA relapse had occurred in only 1 patient, and 8 additional patients receiving peg-IFN had become negative after stopping therapy.…”
Section: Current Therapiesmentioning
confidence: 99%
“…72-week results of this study showed that peg-IFN alpha-2a had a significant antiviral effect for HDV in more than 40% of patients, HDV-RNA relapse had occurred in only 1 patient, and 8 additional patients receiving peg-IFN had become negative after stopping therapy. Adefovir had not affected HDV replication but combination therapy of peg-IFN and adefovir had some advantages in terms of reduction of HBsAg levels [78]. An international study group had found positive correlation between the HBsAg levels and HDV viremia in chronic HDV infection [79].…”
Section: Current Therapiesmentioning
confidence: 99%